PENGARUH PELAYANAN, PENGAWASAN DAN PEMERIKSAAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BADAN YANG DIMODERASI DIGITALISASI ADMINISTRASI PERPAJAKAN - Mimi Yap; Susi Dwi Mulyani (Jurnal Magister Akuntansi Trisakti, 2022)
Taxpayer compliance is a condition that shows the taxpayer fulfills all tax obligations and carries out his tax rights. This study aims to examine and analyze the effect of service, supervision and tax audit on corporate taxpayer compliance which is moderated by digitalization of tax administration. The type of research used is quantitative research, with primary data collected through questionnaires. Respondents from this study were corporate taxpayers who were at the Cengkareng Tax Office. The method of determining the sample using purposive sampling method. The samples that were processed were 100 questionnaires using the Smart PLS 3.0 program. In previous studies, digitizing tax administration as an independent variable and there has never been a study using digitization of tax administration as a moderating variable. The results of this study indicate that tax services and audits have a positive effect on corporate taxpayer compliance, while tax supervision has no effect on corporate taxpayer compliance, and digitalization of tax administration does not strengthen the effect of tax service, supervision and audit. Further researchers can further examine the causes of the lack of effect of tax supervision on taxpayer compliance and the causes of digitalization of tax administration not strengthening the effect of service, supervision and tax audit.